Efficient removal of norfloxacin using nano zerovalent cerium composite biochar-catalyzed peroxydisulfate. (1st December 2022) - Iqbal, Jibran; Shah, Noor S.; Sayed, Murtaza; Rauf, Sajid; Haq Khan, Zia Ul; Niazi, Nabeel Khan; Polychronopoulou, Kyriaki; Howari, Fares; Rehman, Faiza
Abstract: Norfloxacin (NOR), an important antibiotic used for the treatment of different infections which is reportedly causing huge quantity of water pollution and severe environmental issues. In this study, biochar prepared from Phoenix dactylifera roots biomass (PB) and composited with mesoporous nano-zerovalent cerium (nZVCe) was used for treatment of NOR solutions. The various characterization and treatment studies showed successful formation of the nZVCe and PB composite. The nZVCe was found to improve physiological characteristics and catalytic efficiency of PB. The nZVCe/PB composite caused 52% removal of NOR as compared to 23% by the individual PB. The use of peroxydisulfate (PDS) with PB and nZVCe/PB showed further improvement in the removal of NOR and caused 58 and 84% removal efficiencies of NOR by PB/PDS and nZVCe/PB/PDS, respectively. The use of PDS with PB and nZVCe/PB was found to yield ● OH and SO4 ●– which improved degradation of NOR, however, addition of ● OH and SO4 ●– scavengers impeded NOR degradation. The PB was found to have several oxygen functional groups which decomposed PDS into ● OH and SO4 ●– . The nZVCe/PB showed high recovery, reusability, and stability and caused high removal of NOR even at fifth cycle of treatment both in the absence and presence of PDS. The treatment of NOR by nZVCe/PB-catalyzed PDS showed encouraging results under different pH, and varying concentrations of PDS, nZVCe/PB, and NOR as well as in real water samples which suggest potential practical applications of NOR contaminated water. Degradation of NOR resulted into several products and the resulting final product proved to be non-toxic. Graphical abstract: Image 1 Highlights: nZVCe and biochar composite was prepared and nZVCe improved properties of biochar. Biochar and nZVCe/PB effectively decomposed PDS into . ● OH and SO4 ●– . Radical scavengers inhibited role of . ● OH and SO4 ●– in degradation of norfloxacin. The PB and nZVCe/PB effectively degraded norfloxacin in real water also. The composite of biochar and nZVCe showed enhanced stability and reusability.